On the soliton structures of the coupled Higgs model to characterize the nuclear structure of an atom - Badshah, Fazal; Tariq, Kalim U.; İnç, Mustafa; Tang, Lu; Nisar, Sana (Springer, 2023)
In this paper, the dynamical behaviour of the coupled Higgs equation (CHE) is explored analytically, which explains the interaction between mesons and electrons to characterize smooth changes in states of a particle. In this paper, a collection of efficient analytical procedures is employed to develop a variety of intriguing travelling wave structures such as bright, dark, singular, optical, bell shaped, and periodic solitons. Mathematica is used to display the dynamics of various wave shapes in 3D, 2D, and contour structures for a given set of parameters. Furthermore, the consistency of the obtained results is evaluated by validating the stability of the established results. The computational complexities and results show the approaches' lucidity, efficacy, and simplicity, implying their applicability to diverse sets of dynamic and static nonlinear equations governing evolutionary phenomena in computational physics, as well as other practical domains and numerous areas of research.
Keywords: The coupled Higgs equation; The extended Fan sub-equation approach; The improved F-expansion technique; Stability analysis and travelling wave solutions